The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1590/fst.35119
|View full text |Cite
|
Sign up to set email alerts
|

Study on the mechanism and therapeutic effect of Antelope horn treatment on cerebral ischemia reperfusion injury of mouse

Abstract: Materials and methods 2.1 Materials Cells and animals 50 C57BL/6 mice (20-15 g), male, 10 weeks old, body weight 23-25 g, purchased from the Experimental Animal Center in China. Reagents Antelope horn (Chinese Inspection of Biological Products and Drugs) DMEM medium (US BD Biosciences); anti-TNF-α, IL-1β, IFN-β rabbit polyclonal antibodies (Cell Signaling company); rabbit polyclonal anti-β-actin antibody (Santa Cruz Biotechnology, Santa company); fetal bovine serum (US BD Biosciences); mouse anti-human Bax ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Although the multifactorial nature of CHD is well known, genetic factors are considered to be strong determinants of these diseases (Jouki et al, 2020;Lorenzo et al, 2021;Wang & Jin, 2021). Thus encouraging researchers to search for the responsible genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the multifactorial nature of CHD is well known, genetic factors are considered to be strong determinants of these diseases (Jouki et al, 2020;Lorenzo et al, 2021;Wang & Jin, 2021). Thus encouraging researchers to search for the responsible genes.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional chemotherapy drugs, TCMs are less toxic, causing fewer side effects, and are relatively inexpensive. (Mostafa et al, 2021;Wang & Jin, 2021;Morales-Ávila et al, 2020) TCMs have been combined with various conventional clinical therapies to treat HCC and may enhance tumor sensitivity to radiotherapy and chemotherapy, reduce toxicity and side effects, and improve the quality of life and survival rate of patients (Ling et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ischemia of kidney can also lead to necrosis, apoptosis, detachment or differentiation of renal tubular cells (Jung et al, 2009). In addition, reperfusion injury caused by the restoration of blood supply can also lead to local secondary injury, including inflammation, oxidative stress, and apoptosis (Wang & Jin, 2021). With the further study of renal IR, it has been found that IR-mediated AKI is associated with various inflammatory cytokines (Xu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%